Paleomagnetismo de la formación Chon Aike: estabilidad de Patagonia con respecto a América del Sur desde el jurásico tardío - Ruíz González, Víctor (2017)
The aim of this work is to report paleomagnetic results from thirty four si tes of ca 155 Ma ignimbrites in the Deseado Massif, southem Patagonia. After removing site-mean directions with a95 greater than 15º and VGPs located more than 45° from the full mean pole we obtained a palepole located at Lat. 86.3ºS, Long. 183.4ºE (A95= 10.1 º; K= 10; N= 23) which is indistinguishable from Late Jurassic and Early to mid-Cretaceous poles of South America, strongly suggesting that a) Patagonia has been in its present-day position with respect to the main continent since at least the Late Jurassic; and b) the continent has had negligible polar drift during a period of ca 60 m.y. in those times. Applying appropriate reconstructions of the South and Central Atlantic Ocean the results further in - dicate that ~ 155 Ma poles of South America (Patagonia) and North America are compatible with a GAD geometry of the paleofield.